Uncovering the Roots of Obesity- Based Wage Discrimination: The Role of Job Characteristics - Juan Dolado; Luigi Minale; Airam Guerra (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
This paper investigates the roots of potential labour-market discrimination underlying the negative correlation between obesity and hourly wages. Using a panel dataset of white individuals drawn from the U.S. 1997 National Longitudinal Survey of Youth (NLSY97), we test whether residual wage gaps could be attributed to prejudice (taste-based discrimination) and/or statistical discrimination. To this end, we examine how these two types of discrimination hinge on a wide range of obese individuals' specific job and occupational characteristics (drawn from the O*Net Online database). In particular, our analysis sheds light on whether discrimination originates from clients' attitudes, fellow workers or employers. Our findings are consistent with taste-based discrimination against obese females, especially as they become older, in jobs requiring frequent communication with either clients or employers. However, the evidence on this issue is weaker for males. We conjecture that these differences may originate from both an over-representation of males among employers and different image concerns against people of the same gender.
Keywords: J71; J15; J31; J24; I10; 330; Obesity; Wages; Discrimination; Job Characteristics; NLSY97; O*Net Online